Effect Of Nursing Compliance In Washing Hand To Phlebitis Physical Events In Graha Room Hita Husada dr Iskak Tulungagung Hospital - Rusmawati, Aprin; Subekti, Dedi Eko; Saputro, Heri (Journal Of Nursing Practice, 2018)
Bacground: Compliance of nurses in implementing a fixed procedure of nursing actions, including hand washing procedures, became one of the determinants of the success of prevention of nosocomial infections. Noncompliance of nurses in hand washing may lead to an increase in the incidence of phlebitis. Pupose: The influence of nurse compliance in hand washing of phlebitis incidence rate in Graha Hita Husada Room Dr Iskak Tulungagung Hospital. Method: The design of this study was observational with cross-sectional design with population All the nurses in Graha Hita Room Dr. Iskak Tulungagung Hospital number of 54 nurses. The sample is part of population that is 48 respondents with sampling technique by Simple random sampling. The data that have been collected is processed by Linear Regression statistic test with significance α = 0,05. Result: The results showed that most of the respondents had compliance with handwashing compliance, ie 38 respondents (79.2%) and most of the respondents did not experience phlebitis incidence, ie 34 respondents (70.8%). Result of analysis of Linear Regression test got value p-value = 0,000 (<0,05) with value of R Square 0,639 which means reject H0 and accept H1 so that there is relation of nurse compliance in hand washing with number of phlebitis incident in Graha Hita Husada Room dr Iskak Tulungagung Hospital. Conclusion: From the results of this study prove the compliance of nurses in hand washing by applying six steps of hand washing and five moments hand washing correctly and accurately able to prevent the incidence of phlebitis